Neuropeptide Receptors: Novel Targets for HIV/AIDS Therapeutics - Donald R. Branch (MDPI AG, 2011)
The vasoactive intestinal peptide/pituitary adenylyl cyclase-activating polypepetide (VPAC) receptors are important for many physiologic functions, including glucose homeostasis, neuroprotection, memory, gut function, modulation of the immune system and circadian function. In addition, VPAC receptors have been shown to function in vitro to modulate the infection of HIV by a signal transduction pathway that appears to regulate viral integration. In this article, the affects of VPAC stimulation on HIV infection will be reviewed and approaches for the development of HIV/AIDS therapeutics that target these receptors will be described. Novel HIV/AIDS therapeutics are urgently required to stem the continued spread of this disease, particularly in underdeveloped countries. Drug design to inhibit signaling through VPAC1 and stimulate signaling through VPAC2 could lead to alternative therapies for the treatment and/or prevention of HIV/AIDS.